2017
DOI: 10.1177/0731684417702750
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tension in T300/epoxy prepreg winding process on the performance of the bearing composites

Abstract: In recent years, composite bearings are increasingly employed in marine and heavy load situations due to the specific properties of composites. However, for the tape winding composite bearings, the tension in process has not been studied in depth. In this study, a device was manufactured to apply tension to the process and the prepreg tape was T300/epoxy. Specimens with different tension values were selected for the experiment and the autoclave technology was applied to the curing process. Then, the appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This becomes particularly interesting when using highly automated systems and trying to benefit from the inherent upsides from general prepreg forms. Cui et al [108] used T300/epoxy prepreg tape to fabricate composite bearings with filament winding. The study intended to experimentally investigate the influence of the It is important to clearly establish that although filament winding for material system compounds of thermoset matrices is typically associated with the wet technique (as in type IV-FSW tanks), it is also possible to perform tape filament winding using thermoset prepregs (type IV-FST).…”
Section: Winding Methodology: Wet Vs Tapementioning
confidence: 99%
See 1 more Smart Citation
“…This becomes particularly interesting when using highly automated systems and trying to benefit from the inherent upsides from general prepreg forms. Cui et al [108] used T300/epoxy prepreg tape to fabricate composite bearings with filament winding. The study intended to experimentally investigate the influence of the It is important to clearly establish that although filament winding for material system compounds of thermoset matrices is typically associated with the wet technique (as in type IV-FSW tanks), it is also possible to perform tape filament winding using thermoset prepregs (type IV-FST).…”
Section: Winding Methodology: Wet Vs Tapementioning
confidence: 99%
“…This becomes particularly interesting when using highly automated systems and trying to benefit from the inherent upsides from general prepreg forms. Cui et al [108] used T300/epoxy prepreg tape to fabricate composite bearings with filament winding. The study intended to experimentally investigate the influence of the winding tension on finishing and on mechanical and physical properties of bearings.…”
Section: Winding Methodology: Wet Vs Tapementioning
confidence: 99%
“…Therefore, to obtain the better performance of composite, the defects and strength of composite winding products should be lucubrated. Cui et al [10] studied the influence rule of the winding tension on the appearance and performance of bearing composites using the T300/epoxy prepreg tape. Similarly, Okuya et al [11] enhanced the bonding strength of winding products by co-curing the carbon fiber-reinforced plastics strand with end tabs.…”
Section: Introductionmentioning
confidence: 99%
“…In Mikhael Tannous’s paper [ 2 ], a finite element model was proposed for the simulation of the thermo-mechanical tape winding process, and the results showed that mechanical factors and friction play an important role in the winding process. Qing Yu Cui et al [ 14 ] analyzed the function of tension by measuring the physical and mechanical properties of specimens, and considered that the wrinkles and waves on the surface of the T300/epoxy bearing composites can be eliminated using the proper method. The importance of tape placement process parameters was discussed, initially, in Jinxiang Cheng’s article [ 15 ].…”
Section: Introductionmentioning
confidence: 99%